The financial crisis and the dynamics of the money market rates - Nicole Hasler (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2014)
This paper contributes to the ongoing debate about the changing dynamics in the money market rates after 2007. It aims to analyse the interest rate channel of monetary policy transmission until the federal funds target rate reached the zero lower bound. A set of different model explains both long and short run dynamics of U.S. money market rates up to 6 months. I find that secured money market rates move together with monetary policy expectations whereas unsecured interbank rates disconnected from policy rates due to an increase in both credit and liquidity risks.
Keywords: E43; E52; E58; 330; Transmission of Monetary Policy; Financial Crisis; Money Market; Transmission of Monetary Policy; Financial Crisis; Money Market